2019
DOI: 10.3389/fphys.2019.01049
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-Derived Exosomes: Biological Functions and Potential Therapeutic Implications

Abstract: Exosomes, which are membrane-enclosed nanovesicles released by almost all cell types, have been recognized to play important roles in mediating cell-cell communication. In recent years, the physiological and pathological effects of exosomes on cardiovascular disease have been extensively studied. Exosomes can transfer proteins, mRNAs, microRNAs, and other bioactive molecules to recipient cells to influence their biological properties. In recent years, accumulating evidence has suggested that cardiomyocyte-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 104 publications
(117 reference statements)
0
56
0
Order By: Relevance
“…The "cardiac secretome" includes peptides, proteins and coding, and non-coding RNAs released either as free molecules or as microvesicles and exosomes. The expression profile of secreted peptides and proteins-called cardiokines-changes considerably under pathological conditions (40)(41)(42)(43). Cardiokines produced by the failing heart include primary citokines and chemokines of inflammation (mostly with detrimental effects for cardiomyocytes), and also proteins involved in stress response, regulation of apoptosis, tissue repair, cardiac remodeling, and angiogenesis ( Figure 1B).…”
Section: A Cardiac Secretome With Carcinogenic Potentialmentioning
confidence: 99%
“…The "cardiac secretome" includes peptides, proteins and coding, and non-coding RNAs released either as free molecules or as microvesicles and exosomes. The expression profile of secreted peptides and proteins-called cardiokines-changes considerably under pathological conditions (40)(41)(42)(43). Cardiokines produced by the failing heart include primary citokines and chemokines of inflammation (mostly with detrimental effects for cardiomyocytes), and also proteins involved in stress response, regulation of apoptosis, tissue repair, cardiac remodeling, and angiogenesis ( Figure 1B).…”
Section: A Cardiac Secretome With Carcinogenic Potentialmentioning
confidence: 99%
“…Furthermore, exosomes derived from cardiomyocytes were found to carry functional GLUT (GLUT4 and GLUT1) and glycolytic enzymes (lactate dehydrogenase) and were shown to have specialized functions in glucose transport and metabolism in endothelial cells [26]. Many studies have demonstrated that exosomes derived from cardiomyocytes can also carry DNA/RNA [19]. Exosomes secreted by cells derived from cardiomyocytes can improve myocardial function, inhibit cell apoptosis, and promote the proliferation of cardiomyocytes when expressed in a mouse myocardial infarction model, which may be related to the enhancement of the expression of vascular gene SIS [27].…”
Section: Exosomes Derived From Differentmentioning
confidence: 99%
“…When injected into the heart of chronic myocardial perfusion model rats, activated fibroblasts were found to significantly promote angiogenesis and cardiac protection [34]. Recent evidence established that exosomes secreted from cardiomyocytes can deliver a wide variety of biomolecules into other types of cells and regulate gene expression in these cells [19].…”
Section: Exosomes Derived From Differentmentioning
confidence: 99%
“…All of these cell types use extracellular molecules to communicate with each other and any alteration either in the composition of the exosomal cargo or its machinery can affect cardiac homeostasis, leading to disease [13]. Cardiac exosomes are oversecreted as a consequence of stressing factors such as angiotensin II production, hypoxia, inflammation, or injury [51]. Recent literature has shown that exosomes may modify cardiac repair and the fate of fibrosis via the modulation of fibroblast function and likely contribute to obesity cardiomyopathy in which microRNAs seem to play a crucial role [13].…”
Section: Morphological and Molecular Characteristics Of The Heart In mentioning
confidence: 99%